2020
DOI: 10.1088/1748-9326/ab8659
|View full text |Cite
|
Sign up to set email alerts
|

The world’s growing municipal solid waste: trends and impacts

Abstract: Global municipal waste production causes multiple environmental impacts, including greenhouse gas emissions, ocean plastic accumulation, and nitrogen pollution. However, estimates of both past and future development of waste and pollution are scarce. We apply compositional Bayesian regression to produce the first estimates of past and future (1965–2100) waste generation disaggregated by composition and treatment, along with resultant environmental impacts, for every country. We find that total wastes grow at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
152
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(166 citation statements)
references
References 43 publications
3
152
0
11
Order By: Relevance
“…The water volume of such bottles could fill up 2,400 Olympic stadiums, 4.8 million Olympic size swimming pools, or 40 billion bathtubs. This is also the weight of 3.4 million adult blue whales or 1,376 Empire State Buildings [75].It can be concluded that the solid waste has emerged as a huge potential problem for the universe and scientific community. In order to view the situation more clearly, the universal solid waste can be classified in to two subheadings viz.…”
Section: Usa 16mentioning
confidence: 99%
“…The water volume of such bottles could fill up 2,400 Olympic stadiums, 4.8 million Olympic size swimming pools, or 40 billion bathtubs. This is also the weight of 3.4 million adult blue whales or 1,376 Empire State Buildings [75].It can be concluded that the solid waste has emerged as a huge potential problem for the universe and scientific community. In order to view the situation more clearly, the universal solid waste can be classified in to two subheadings viz.…”
Section: Usa 16mentioning
confidence: 99%
“…The key question we pose when we start modeling a municipal solid waste (MSW) management system is how much waste will be generated today, in a year and in 10-20 years. Since the amount of municipal waste is closely related to the number of inhabitants, it is necessary to know not only demographic trends, but also changes in the amount and fractions of municipal waste and these amounts are closely related to the standard of living, i.e., the level of residents' income [2][3][4][5][6]. For many years, attempts have been made to model and predict the quantity and fractions of municipal waste [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Waste is an unavoidable thing that is created due to human activities, urbanization, development of living standards, and economic evolution [1]. These changes in human activities increase the volume of waste generation as well as the category of waste.…”
Section: Introductionmentioning
confidence: 99%
“…The world is producing 7-9 billion tonnes of waste yearly [1,2]. In 2016, around two billion tonnes of municipal solid waste were generated [1]. This wastage is affecting our entire environment and all human beings as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation